Analisa Kelayakan Investasi Pembangunan Fasilitas Pemanfaatan Alternatif Bahan Baku dan Bahan Bakar di PT. X - Bekti Nugrahadi; Supriyanto Wibowo; Agung Widiyanto Fajar Sutrisno; Erna Indriastiningsih (Program Studi Teknik Industri Universitas Setia Budi, 2025)
Indonesia's manufacturing sector has grown, which affects the amount of waste produced. Waste must be managed by the companies that generate it; if they are unable to do so, the waste may be turned over to a third party. PT. X is a business that works in manufacturing, particularly in the cement sector. PT. X is dedicated to producing fuel, raw materials, and energy sources that are efficient in its production process. In order to meet the company's long-term plan goal of increasing the substitution of energy sources, raw materials, and fuel, facilities for using waste as raw materials and alternative raw materials must be built. The purpose of this study is to obtain the results of a feasibility study on the investment in the construction of these facilities. The data used in this study are primary data in the form of waste potential, company technical data, investment data, operational data and interviews as secondary data. The methods used in this study are Net Present Value (NPV), Payback Period (PP), and Internal Rate Of Return (IRR). The results of this study obtained a payback period value of 5 years 7 months, an NPV of 6,784,925,409 (NPV > 0), and an IRR of 15.85% so that the investment is feasible to continue.